2000
DOI: 10.1037/h0087823
|View full text |Cite
|
Sign up to set email alerts
|

The National Lesbian Family Study: 3. Interviews with mothers of five-year-olds.

Abstract: This third report from a longitudinal study of lesbian families presents data obtained from interviews with mothers of five-year-old children conceived by donor insemination. Results indicated that 87% of the children related well to peers, 18% had experienced homophobia from peers or teachers, and 63% had grandparents who frankly acknowledged their grandchild's lesbian family. Of the original couples, 31% had divorced. Of the remainder, 68% felt that their child was equally bonded to both mothers. Concerns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
209
1
21

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(245 citation statements)
references
References 19 publications
11
209
1
21
Order By: Relevance
“…However, the children also reported that it was hard for some peers to understand that someone has two mothers without having a father. Similar findings were reported in the National Lesbian Family Study of Gartrell et al (2000). Golombok et al (2003) examined children's peer relationships in 39 lesbian and 134 heterosexual families.…”
Section: Methodssupporting
confidence: 65%
“…However, the children also reported that it was hard for some peers to understand that someone has two mothers without having a father. Similar findings were reported in the National Lesbian Family Study of Gartrell et al (2000). Golombok et al (2003) examined children's peer relationships in 39 lesbian and 134 heterosexual families.…”
Section: Methodssupporting
confidence: 65%
“…Previous research into the experiences of parents who have formed a family using donor conception has largely focused on anonymity and disclosure (Almack, 2006;Becker et al, 2005;Bos et al, 2003;Brewaeys et al, 1993;Burr, 2009;Cook et al, 1995;Donovan and Wilson, 2008;Gartrell et al, 2000;Grace et al, 2008;Haimes and Weiner, 2000;Nachtigall et al, 1997;Scheib et al, 2003;Shehab et al, 2008;Suter et al, 2008;Touroni and Coyle, 2002;Werner and Westersthål, 2008) and, more recently, on the experiences of these parents and their offspring with regard to searching for their donor and half-siblings (Blyth, 2012;Freeman et al, 2009;Jadva et al, 2010). Despite this volume of research, the experiences and concerns of the recipients of donor spermatozoa regarding how the sperm banking industry operates has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a time during which teenagers are particularly sensitive to disapproval from peers (Rubin et al 2006). Because lesbian mothers anticipate that their offspring may be subjected to homophobic stigmatization, protective responses include careful supervision of their offspring's routine activities and leisure time (Gartrell et al 1999(Gartrell et al , 2000. As their offspring enter adolescence, it is not known whether lesbian parents extend this monitoring to impose even stricter controls than heterosexual parents.…”
Section: Introductionmentioning
confidence: 99%